2020
DOI: 10.1177/0017896919898738
|View full text |Cite
|
Sign up to set email alerts
|

New Caledonian biology teachers’ opinions about vaccination: Preliminary findings

Abstract: Objective: Vaccine hesitancy is increasing worldwide and the World Health Organisation has declared it to be one of the 10 threats for global health in 2019. Lack of confidence in vaccines and fear of side effects seem to be the key reasons. Education may help restore confidence, and middle and high school biology teachers may have a particularly powerful role in countering vaccine hesitancy. The aim of this study was to compare biology teachers’ opinions about vaccination with those of other teachers. Design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…Analysing obtained data, can see that, in accordance with the observations of Zeyer (2019), andFrayon (2020), three clearly differentiated groups have been obtained, some that believe in one or more CTs, others that do not, and a considerable group of hesitant (40.1%). This hesitant group is an optimal work group to promote the provaccination discourse; since, it is usually more influenced by the arguments in pro than by the arguments against (Zeyer (2019), and they tend to opt in one direction or another depending on the context, time, place, complacency, convenience and trust (Salmon, et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…Analysing obtained data, can see that, in accordance with the observations of Zeyer (2019), andFrayon (2020), three clearly differentiated groups have been obtained, some that believe in one or more CTs, others that do not, and a considerable group of hesitant (40.1%). This hesitant group is an optimal work group to promote the provaccination discourse; since, it is usually more influenced by the arguments in pro than by the arguments against (Zeyer (2019), and they tend to opt in one direction or another depending on the context, time, place, complacency, convenience and trust (Salmon, et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…We explored if the educational training background was associated with vaccine confidence and found that those with an educational background in a scientific discipline (e.g., biology, engineering) had higher vaccine confidence, for both sub-scales of the VHS. The association between formal scientific training and higher vaccine confidence underscores previous work, reporting on the role of scientific education and science literacy being associated with increased vaccination and vaccine confidence [ 8 , 28 ]. In a highly educated population of teachers, the association between formal scientific training and increased vaccine confidence suggests that a public health partnership opportunity with science teachers to increase vaccine knowledge may be a successful strategy to increase vaccine confidence among teachers and students [ 8 ].…”
Section: Discussionsupporting
confidence: 61%
“…There is currently limited information on the general characterization of vaccine confidence in public-school teachers, with preliminary findings indicating the overall teachers are supportive of vaccination [ 7 , 8 ], As such, there continues to be a need to measure and characterize vaccine confidence, explore how teachers perceive their role within the school-based immunization program, and identify potential for opportunities to engage teachers more in school-based immunization programs. Increasing our understanding of vaccine confidence, in relation to the role teachers play in immunization decision making, will inform potential future interventions to improve vaccine uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines are sometimes taught in school science as a topic in their own right, often with the ultimate aim of improving public health through enhanced vaccine uptake (Frayon, 2020 ; García-Toledano et al, 2022 ). Often, though, they are taught as examples of the application of science, after such topics as the immune system, disease and DNA have been taught.…”
Section: Contextmentioning
confidence: 99%